THE INFLUENCE OF LEARNING METHOD AND COGNITIVE STYLE MODELS ON CLASS IV STUDENT LEARNING OUTCOMES - Rita Afrina; Bambang Sahono; Turdjai Turdjai (UNIB Press, 2018)
The objective of this research is to know the effect of cooperative learning method (Jigsaw and TPS) and cognitive style on students’ learning outcomes of science. The research was applied to 36 students on fourth grade of SDN 07 Kota Bengkulu, which are 18 students applied jigsaw and 18 students applied TPS. This research used an experimental method with 2 x 2 factorial design. Data was collected through questionnaires and tests. Data analysis used two-way analysis of variance (ANOVA) and t-test. The results of this research are: (1) learning outcomes of students applied jigsaw are higher than learning outcomes of students applied TPS; (2) learning outcomes between field independent students do not have a significant difference with field dependent students; (3) there is an interaction between learning method and the cognitive style of students towards the students’ learning outcomes; (4) Learning outcomes of field independent students applied jigsaw are higher than field independent students applied TPS; (5) learning outcomes between field dependent students applied jigsaw do not have a significant difference with field dependent students applied TPS.